2011
DOI: 10.1038/nature10200
|View full text |Cite
|
Sign up to set email alerts
|

Morphological evolution caused by many subtle-effect substitutions in regulatory DNA

Abstract: Summary Morphology evolves often through changes in developmental genes, but the causal mutations, and their effects, remain largely unknown. The evolution of naked cuticle—rather than trichomes—on larvae of Drosophila sechellia resulted from changes in five transcriptional enhancers of shavenbaby, a gene encoding a transcription factor that governs trichome morphogenesis. Here we show that the function of one of these enhancers evolved through multiple single nucleotide substitutions that altered both the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
188
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 202 publications
(207 citation statements)
references
References 39 publications
13
188
0
1
Order By: Relevance
“…This observation indicates that at least one of the clusters affects the activity of E6 and that at least one other change (other than the 14 targeted) contributes to the function of the E6 region. Four of the seven clusters caused small changes in trichome numbers (figure 4c), ranging from 5% to 30% of the total effect [21]. The sum of the effect sizes of individual clusters did not equal the effect size of the construct with all 14 changes, indicating the existence of epistatic interactions between sites.…”
Section: Genetic Changes In Multiple Enhancers and Multiple Changes Wmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation indicates that at least one of the clusters affects the activity of E6 and that at least one other change (other than the 14 targeted) contributes to the function of the E6 region. Four of the seven clusters caused small changes in trichome numbers (figure 4c), ranging from 5% to 30% of the total effect [21]. The sum of the effect sizes of individual clusters did not equal the effect size of the construct with all 14 changes, indicating the existence of epistatic interactions between sites.…”
Section: Genetic Changes In Multiple Enhancers and Multiple Changes Wmentioning
confidence: 99%
“…Alignment of the E6 region from multiple species revealed 14 genetic changes that were uniquely derived in the D. sechellia sequence (figure 4b). Further sequence analysis showed that the D. sechellia region containing the 14 changes had evolved rapidly, consistent with the idea of positive selection in the D. sechellia lineage [21]. Some of these 14 sites were located very close to one other, and we therefore decided to test the effects of groups of these sites, resulting in seven candidate 'clusters' (figure 4b).…”
Section: Genetic Changes In Multiple Enhancers and Multiple Changes Wmentioning
confidence: 99%
“…For instance, the regulatory information needed for embryonic expression of S. purpuratus endo16 appears to be circumscribed to 2,300 base-pairs (Yuh et al, 2001). In contrast, several developmental genes in metazoan genomes have cis-regulatory elements scattered over tens or hundreds of kilobases (Maeda and Karch, 2009;Frankel et al, 2011;Montavon et al, 2011;Visser et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it is widely recognized in the cis-regulation community that, often, small enhancer elements do not faithfully recapitulate native expression patterns (Barolo, 2012). Frequently, reporter constructs drive expression in the wrong cells, a fact known as ''ectopic expression'' (Summerbell et al, 2000;Chao et al, 2010;Prazak et al, 2010;Frankel et al, 2011;Perry et al, 2011). It is also common to observe reporter expression which does not coincide temporally with that of the native gene, a phenomenon often referred as ''heterochronic expression'' (Adachi et al, 2003;Lin et al, 2010;Prazak et al, 2010;Frankel et al, 2011;Ludwig et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…deleterious pleiotropy). An example of such a gene is shaven-baby (svb), associated with loss of larval trichomes in multiple Drosophila species [74,75]. The expression of svb in a cell is enough to induce development of a trichome structure from a precursor cell.…”
Section: The Hourglass Shape Of Networkmentioning
confidence: 99%